Asymmetric total synthesis of (+)-tubingensin A. Issue 1 (25th November 2022) - Zhai, Hongbin; Liu, Dong; Wang, Taimin
Abstract : A nine-step asymmetric total synthesis of (+)-tubingensin A has been realized. Abstract : A nine-step asymmetric total synthesis of (+)-tubingensin A has been realized. The synthesis features (a) an intramolecular Heck reaction to install the C20 quaternary carbon center thus establishing the key vicinal quaternary stereocenter motif present in the natural product and (b) a late-stage Zweifel olefination applied to side chain elongation.